Prediction of immunogenicity of Rh antigens using in silico analysis of binding to human leukocyte antigen peptide, Basic/Translational Research - Hee-Jeong Youk; Yong-Joon Cho; Yong-Hyun Han; Seong Who Kim; Dae-Hyun Ko (PLoS ONE, 2025)
The association between human leukocyte antigen (HLA) types and blood group alloimmunization remains unclear. Previous studies have predominantly focused on predicting immunization events in cancer immunotherapy, but not blood group antigens. In this study, we investigated whether HLA peptide binding could predict the immunogenicity of blood group antigens. We performed in silico binding analysis of Rh antigens and representative HLA class II alleles using NetMHCpan-4.1 and NetMHCIIpan-4.1 algorithms. The distribution of strong binding regions (hotspots) differed across HLA loci and ethnic groups. In particular, the RhD and RhCE antigens showed several distinct hotspots for the HLA-DRB, -DQA-DQB, and -DPA-DPB HLA class II peptides. A hotspot of RHD*01W.1 in HLA-DRB had a substitution in p.Val270Gly. The number of hotspots and core amino acids was different for each HLA locus, and the amino acid regions (exofacial, transmembrane, and intracellular region) differed among the hotspots. Our findings underscore the significance of immunogenicity between the Rh antigens and HLA-DR, suggesting the potential clinical utility of predicting antibody development in blood transfusions. This in silico approach offers novel insights into understanding and managing alloimmunization events, particularly in patients with multiple alloantibodies when blood transfusion is required.